Investigating The Mediating Role Of Work Engagement In The Relationship Between Personality And Work Performance Among Freelancers - Ashraf, Rabbia; Hussain, Muhammad; haq, Ahtesham ul; Ullah, Asmat; Fatima, Ishrat (Migration Letters, 2024)
Study aim to explore the mediating role of work engagement between personality and work performance in freelancers. 130 (male=93, female =37) freelancers of mean age 36 (SD=.45) were recruited from various private coworking spaces. Results found out that personality traits of agreeableness, conscientiousness and openness are significantly positively related with work performance. Agreeableness emerged as positive predictors of total score of work performance and its subscale contextual performance but as negative predictor of counterwork productive behavior. Consciousness personality traits also negatively predicted counterwork productive behavior. Openness trait was found to be positive predictor of contextual work performance and negative predictor of counterwork productive behavior and neuroticism positively predicted counterwork productive behavior. Result also found that work engagement mediates the relationship between autotelic personality and work performance.